Analisis Privasi Dan Publikasi Postingan Media Sosial Di Kalangan Orang Muda Menurut Interaksionisme Simbolik Herbert Blumer - Ranubaya, Fransesco Agnes; Endi, Yohanes (Jayapangus Press, 2023)
Social media is a popular tool for young people. Half the lives of young people are poured into social media. This is evidenced by statistical data that states that young people can spend a lot of time just to access social media. All kinds of affairs have shifted from conventional means to computerization. With the emergence of various kinds of limelight that exist on social media, young people are increasingly immersed in trends both positively and negatively. There are two general trends that young people make in social media, namely regarding privacy and the publication of posts on social media. This writing uses qualitative research methods using data collection techniques through interviews and documentation studies. The purpose of this study is to know the form of the phenomenon of publication and privacy of posts on social media for young people, and also to know the analysis of privacy and publication of social media posts among young people according to Herbert Blumer's Symbolic Interactionism. This type of research uses qualitative research methods using data collection techniques through literature studies to strengthen research arguments and interviews with five resource persons from young people with interview guide instruments and recording tools. The results of this study show strong reasons for choosing privatization, namely avoiding the curiosity of others, not everything must be published, knowing the limits to minimize crime seeds from irresponsible parties and preventing crimes such as account hacking, taking photos from social media for fraud.